Therapeutic and economic efficiency of anti-helminthics in treatment of gastro-intestinal helminthiasis of cows - Кручиненко, О. В.; Прус, М. П.; Шабалін, О. М. (Scientific Progress & Innovations, 2012)
The research results of therapeutic and economic efficiency of albendazole Ultra 10%, kombitrem and rafenzol are shown below. It was found that by simultaneous parasitizing of paramfistom, dikrocelij, fasciol and strongilat in the digestive organs kombitrem and rafenzol show 100 % extens-andintenseffect, and albendazole Ultra 10 %, respectively 90 % and 75 %. Deworming of cows provides the growth of milk productivity – when treated with Ultra 10% (albendazol) milk productivity is 14.3% higher, with kombitremom – 17.6% and rafenzolom – 20.6%.The selling of milk from the cows of three experimental groups gave additional 1038 UAH profit.